The Values of Peace in Islamic Education - Diaya Uddeen Deab Mahmoud Alzitawi (AL-WIJDÁN: Journal of Islamic Education Studies, 2022)
Islam holds significant values regarding to peace among its followers and believers. Some typical values are bonding of brotherhood, spreading (Salam), exchanging gifts, feeding food, helping the distressed and the rights of the dhimmi. Islam emphasizes the meanings and values of peace in dealing with non-Muslim countries and societies, by enacting regulations governing the relationship of the Islamic state with other non-Muslim countries. Peace in the Islamic concept does not negate the presence of disagreement and division, even arguments between its followers or even with non-Muslim countries and societies. The researcher has analyzed a few samples of historical facts in which Muslims have applied their core values of peace quoted from Islamic legislation in their dealings with their Muslim brothers and also with non-Muslim sects and countries. The researcher used the descriptive historical method to analyze the data that He studied, with that outcome, the researcher presented a set of results. An important factor that can be addressed is the state of non-peace that prevails in humanity during our present time. Eventually, this leads to non-compliance with the divine legislations that are justified in the Qur’an, the Sunnah, and also through the lives of the Companions and their followers. Moreover, this article has recorded a significant result: the values of peace in Islamic education. It contributed to spreading a state of peace and no war between non-Muslims while Muslims lived as minorities in non-Muslim societies. Especially those who live as minorities in non-Muslim communities.   Keywords: Peace, Education, Islamic values. Islamic education